1994
DOI: 10.1093/oxfordjournals.humrep.a138607
|View full text |Cite
|
Sign up to set email alerts
|

Differential RNA fingerprinting as a tool in the analysis of spermatozoal gene expression

Abstract: The apparent decline in human male fertility and the concomitant increase in testicular pathology have prompted discussion of the underlying molecular mechanisms which may underpin these observations. While monitoring the expression of protamine-2 genes in the human ejaculate, we found a representative complement of sperm mRNAs following sequence-independent amplification of reverse-transcribed cDNAs with the polymerase chain reaction (RT-PCR). The revelation of unique sperm-derived PCR products using this met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 0 publications
1
49
0
1
Order By: Relevance
“…The purity of these samples was estimated by RT-PCR using protamine-2 specific primers [13] that produce a 310 bp in samples containing genomic DNA (not shown). The reverse-transcribed cDNA amplicon is 148 bp long.…”
Section: Patients and Rna Samplesmentioning
confidence: 99%
“…The purity of these samples was estimated by RT-PCR using protamine-2 specific primers [13] that produce a 310 bp in samples containing genomic DNA (not shown). The reverse-transcribed cDNA amplicon is 148 bp long.…”
Section: Patients and Rna Samplesmentioning
confidence: 99%
“…RNA identification in mature sperm has been performed using techniques based on the detection of RNA by means of PCR after reverse transcription [59]. Our study investigated the expression of the FasL gene in ejaculated sperm and demonstrated that expression of the FasL gene was higher in adolescents with varicocele.…”
Section: Discussionmentioning
confidence: 95%
“…This laboratory's earliest foray into sperm RNA was in its assessment as a convenient and sensitive marker of successful (or unsuccessful) human vasectomy [55]. We also reasoned that if ejaculate spermatozoa could provide equivalent information on what underlies a nonobstructive subfertile or infertile phenotype, a noninvasively obtained semen sample was surely a preferable and more widely acceptable option to testis biopsy.…”
Section: Historical Contextmentioning
confidence: 99%